Vitamin C supplementation as adjuvant analgesic therapy in post-operative pain management in patients undergoing surgical decompression in a case of prolapsed intervertebral disc - Mahajan, Neetin P.; Narvekar, Mrugank A.; Chandanwale, Ajay S.; Gadod, Lalkar L.; Prasannakumar, G. S. (International Journal of Research in Medical Sciences, 2021)
Background: The management of postoperative pain has been a major challenge for the operating surgeons. Vitamin C has shown analgesic effects in specific clinical conditions, reducing patient suffering and improving the quality of life. The objective of this study was to evaluate the efficacy of vitamin C as an adjuvant in postoperative pain management and its effect on analgesia requirements in patients undergoing spinal decompression surgery. Methods: The present study was a prospective study of 50 patients aged 30-60 years with low back pain due to prolapsed intervertebral disc requiring surgical decompression, conducted in a tertiary care institute from 2018 to 2020. All patients underwent open discectomy. 25 patients each were randomized into two groups, those that were given vitamin c supplementation (group A) and those that weren’t (group B). The patients were then followed up 1st, 2nd, 4th, and 6th week and the pain was graded at each follow-up according to the NRS scale. The total amount of diclofenac sodium consumed in the 6 weeks was calculated. Results: The mean NRS (A vs B) at 2 (2.68 vs 3.56) and 4 (0.88 vs 1.48) weeks follow-up showed a statistically significant difference between the two groups, but the difference was not significant at 6 (0.16 vs 0.36) weeks follow up. The difference in the consumption of analgesic (3.56 vs 5.46) at 6 weeks was statistically significant. Conclusions: In this clinical outcome-based study, we suggest that for postoperative pain management, vitamin C acts as an efficacious adjuvant with a dose-sparing effect on the consumption of analgesics.